Answer:A
Step-by-step explanation:
Answer:
x > -3/7
Step-by-step explanation:
6x - 2(x + 2) > 2 - 3(x + 3)
Distribute the two and three inside the parenthesis.
6x - 2x - 4 > 2 - 3x - 9
Combine like terms.
4x - 4 > -3x - 7
Add 4 to both sides.
4x > -3x - 3
Add 3x to both sides.
7x > -3
Divide both sides by 7.
x > -3/7
Answer:
If a, b and c are in arithmetic progression, that means that a + c = 2b. So a + b, a + c and b + c are also in arithmetic progression.
This might help.
Answer:
y = 12-(61) is the answer !!
Answer:
y= 5x/7 -27/7
if they are parallel there gradient is the same
m1=m2
y-y1=m(x-x1)
plug in the gradient and points E
y-(-3)=5/7( x-4)
y= 5/7(x) -20/7 +3
final answer
y= 5/7(x) +1/7